2011
DOI: 10.1017/s1041610211000974
|View full text |Cite
|
Sign up to set email alerts
|

Frontotemporal atrophy associated with paranoid delusions in women with Alzheimer's disease

Abstract: Frontotemporal atrophy is associated with paranoid delusions in females with AD. Evidence of sex differences in the neuroanatomical correlates of delusions as well as differences in regional involvement in different types of delusions may be informative in guiding management and treatment of delusions in AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 31 publications
3
32
1
Order By: Relevance
“…A magnetic resonance imaging study in AD+P demonstrated reduced frontotemporal cortical thickness in women, but not men, with AD+P. (Whitehead et al, 2012) A voxel-based analysis of whole brain cerebral perfusion was undertaken in a large sample of AD+P (N=51) and AD−P (N=52) subjects. (Moran et al, 2008) In this study, perfusion patterns were vastly different between AD+P females and AD+P males.…”
Section: Discussionmentioning
confidence: 99%
“…A magnetic resonance imaging study in AD+P demonstrated reduced frontotemporal cortical thickness in women, but not men, with AD+P. (Whitehead et al, 2012) A voxel-based analysis of whole brain cerebral perfusion was undertaken in a large sample of AD+P (N=51) and AD−P (N=52) subjects. (Moran et al, 2008) In this study, perfusion patterns were vastly different between AD+P females and AD+P males.…”
Section: Discussionmentioning
confidence: 99%
“…Reductions in frontal cortex gray matter were most consistently reported across studies, although parietal cortex was also affected. One study also reported sex differences in AD + P with only female subjects showing reduced cortical thickness in left orbitofrontal, superior temporal, and insular regions (64). Magnetic resonance imaging has also been used to evaluate whether white matter hyperintensities associate with AD + P, with inconsistent results (Table S3 in Supplement 1).…”
Section: Neuroimaging Studies Of Psychosis In Alzheimer’s Diseasementioning
confidence: 99%
“…A number of magnetic resonance imaging studies of gray matter volume have been reported in AD + P, using both region of interest and voxel-based comparisons (6164). Studies were consistent in demonstrating an association of AD + P with decreased gray matter volumes (Figure 3).…”
Section: Neuroimaging Studies Of Psychosis In Alzheimer’s Diseasementioning
confidence: 99%
“…Patients with AD, particularly women showing paranoid delusions, had cortical atrophy in the left medial orbitofrontal, left superior temporal cortices, and the left insula, independent of cognitive decline 3 .…”
mentioning
confidence: 94%